STUDENTS’ ABILITY IN DESCRIBING THEMSELVES THROUGH SYMBOLS - Pusparini, Diah Anita (Proceeding of International Conference on Islamic Education (ICIED); Vol 2 No 1 (2017): Proceeding of International Conference on Islamic Education (ICIED), 2017)
Among the various numbers of English learning skills, writing is considered important component in expressing written thoughts. This is proven by many students still difficult to start and afraid in making grammatical mistakes in writing by using English. It seemed that students’ problem in writing will still going on considering most writing classes nowadays are tend to have a full-tense and quiet atmosphere. Thus, one of the ways which can be used to arouse the students’ interest in writing is by motivating them to write any information about themselves in certain topics. In order to manage a supportive situation for students to write freely, symbols can be used to gain the students’ creativity and willingness to write. In fact, symbols are things that represent or stand for something else, especially representing something abstract. In this writing activity, the students were asked to draw some symbols which represent their characteristics, dreams, hopes, or things around them. This way, students were having some time to think over the paragraph they would write after drawing the symbols. Through this consideration, in this research based article, the researcher would like to know whether symbols can help the students in describing themselves easier. This research was done through the Lesson Study activity of the English Education Study Program at STKIP PGRI Pasuruan especially for the second semester students.